Molecular Mechanisms of Vascular Health: Insights From Vascular Aging and Calcification. Issue 1 (22nd November 2022) - Sutton, Nadia R.; Malhotra, Rajeev; St. Hilaire, Cynthia; Aikawa, Elena; Blumenthal, Roger S.; Gackenbach, Grace; Goyal, Parag; Johnson, Adam; Nigwekar, Sagar U.; Shanahan, Catherine M.; Towler, Dwight A.; Wolford, Brooke N.; et al.
Abstract : Cardiovascular disease is the most common cause of death worldwide, especially beyond the age of 65 years, with the vast majority of morbidity and mortality due to myocardial infarction and stroke. Vascular pathology stems from a combination of genetic risk, environmental factors, and the biologic changes associated with aging. The pathogenesis underlying the development of vascular aging, and vascular calcification with aging, in particular, is still not fully understood. Accumulating data suggests that genetic risk, likely compounded by epigenetic modifications, environmental factors, including diabetes and chronic kidney disease, and the plasticity of vascular smooth muscle cells to acquire an osteogenic phenotype are major determinants of age-associated vascular calcification. Understanding the molecular mechanisms underlying genetic and modifiable risk factors in regulating age-associated vascular pathology may inspire strategies to promote healthy vascular aging. This article summarizes current knowledge of concepts and mechanisms of age-associated vascular disease, with an emphasis on vascular calcification.